Studies of Bolivian Ptiliidae (Coleoptera) 1: The genus Cissidium Motschulsky with six new species - Darby, Michael (Zootaxa, 2015)
This is the first report on a collection of Ptiliidae from Bolivian forest leaf litter made by Dr Petr Baňař of the Brno Museum (Czech Republic). Six new species in the genus Cissidium Motschulsky, are described and figured: C. amboroensis, sp. n., C. globosum, sp. n., C. elongatum, sp. n., C. lisae sp. n., C. petri sp. n. and C. tigrum, sp. n.. The relationship of Cissidium to Dacrysoma Grebennikov and its position in the tribe Discheramocephalini is discussed, and the generic description revised so as to encompass all valid species.